Odontogenic myxomas harbor recurrent copy number alterations and a distinct methylation signature - Kleijn, Tony G.; Ameline, Baptiste; Schreuder, Willem H.; Kooistra, Wierd; Doff, Jan J.; Witjes, Max; Pichardo, Sarina E. C.; Lausová, Tereza; Koppes, Sjors A.; van den Hout, Mari F. C. M.; van Engen-van Grunsven, Ilse C. H.; Flucke, Uta E.; et al. (The American journal of surgical pathology, 2024)
Odontogenic myxoma is a rare, benign, and locally aggressive tumor that develops in the tooth-bearing areas of the jaw. The molecular mechanisms underlying odontogenic myxomas are unknown and no diagnostic markers are available to date. The aim of this study was to analyze DNA methylation and copy number variations in odontogenic myxomas to identify new molecular signatures for diagnostic decision-making. We collected a cohort of 16 odontogenic myxomas from 2006 to 2021 located in the mandible (n = 10) and maxilla (n = 6) with available formalin-fixed paraffin-embedded or fresh frozen tumor tissue from a biopsy or resection material. Genome-wide DNA methylation and copy number variation data were generated from 12 odontogenic myxomas using the Illumina Infinium Methylation EPIC array, interrogating >850,000 CpG sites. Unsupervised clustering and dimensionality reduction (Uniform Manifold Approximation and Projection) revealed that odontogenic myxomas formed a distinct DNA methylation class. Copy number profiling showed recurrent whole-chromosome gains (trisomies) of chromosomes 5, 8, and 20 in all cases, and of chromosomes 10, 12, and 17 in all except one case. In conclusion, odontogenic myxomas harbor recurrent copy number patterns and a distinct DNA methylation profile, which can be used as an additional diagnostic tool in the appropriate clinical and radiologic context. Further research is needed to explain the genetic mechanisms caused by these alterations that drive these locally aggressive neoplasms.
Gesehen am 10.03.2025